A Theoretical Study on Charge Transfer and Hyperpolarizability of (S)-2-amino-3-(3,4-dihydroxyphenyl)-2-methyl-propanoic Acid - Chaudhary, Tarun; Chaudhary, Manoj Kumar; Joshi, Bhawani Datta (Journal of Nepal Physical Society, 2022)
The DFT approach was used to investigate the antihypertensive molecule (S)-2-amino-3-(3,4-dihydroxyphenyl)- 2-methyl-propanoic acid at the B3LYP/6-311++G(d,p) level of theory. The electron-hole analysis of three excited states has been performed, in which the maximum charge transfer length (2.727Å) has been calculated for the first excited state and the minimum for the third excited state (1.626 Å). On the other hand, the electron-hole overlap is found to be almost negligible for the first excited state and it is found to be maximum for the second excited state. The variation of thermodynamic properties with temperature is studied. The correlation graphs are obtained between the thermodynamic quantities (heat capacity, enthalpy, entropy) and temperature with a very high value of R2 (>0.99). The values of dipole moment, mean polarizability, anisotropy of polarizability, first hyperpolarizability and second hyperpolarizability are found to be 3.5250 Debye, 12.6980×10−24esu, 19.8162×10−24esu, 0.9017×10−30esu and -0.0412×10−35esu, respectively. These values are higher than the value of urea.